Genes transcribed in the salivary glands of female Rhipicephalus appendiculatus ticks infected with Theileria parva - Nene, Vishvanath M.; Lee, D.; Kang'a, S.; Skilton, Robert A.; Shah, Tushaar; Villiers, Etienne P. de; Mwaura, S.; Taylor, D.; Quackenbush, J.; Bishop, Richard P. (Elsevier, 2004)
We describe the generation of an auto-annotated index of genes that are expressed in the salivary glands of four-day fed female adult Rhipicephalus appendiculatus ticks. A total of 9162 EST sequences were derived from an uninfected tick cDNA library and 9844 ESTs were from a cDNA library from ticks infected with Theileria parva, which develop in type III salivary gland acini. There were no major differences between abundantly expressed ESTs from the two cDNA libraries, although there was evidence for an up-regulation in the expression of some glycine-rich proteins in infected salivary glands. Gene ontology terms were also assigned to sequences in the index and those with potential enzyme function were linked to the Kyoto encyclopedia of genes and genomes database, allowing reconstruction of metabolic pathways. Several genes code for previously characterized tick proteins such as receptors for myokinin or ecdysteroid and an immunosuppressive protein. cDNAs coding for homologs of heme-lipoproteins which are major components of tick hemolymph were identified by searching the database with published N-terminal peptide sequence data derived from biochemically purified Boophilus microplus proteins. The EST data will be a useful resource for construction of microarrays to probe vector biology, vector–host and vector–pathogen interactions and to underpin gene identification via proteomics approaches.